Allometric description of ostrich (Struthio camelus var. domesticus) growth and development - Kritzinger, Werne Jacobus (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MScAgric (Animal Sciences))--University of Stellenbosch, 2011.